Demography of a high‐density tiger population and its implications for tiger recovery. Issue 7 (20th May 2019) - Bisht, Shikha; Banerjee, Sudip; Qureshi, Qamar; Jhala, Yadavendradev
Abstract: Prioritizing conservation of source populations within landscapes is proposed as a strategy for recovering tigers globally. We studied population dynamics of tigers in Corbett National Park (CNP) in Indian Terai, which harbours the largest and highest density tiger population in any protected area of the world. Through population viability models, we demonstrate the importance of CNP in tiger recovery within western Terai . We camera trapped 521 km 2 of CNP using open population capture–mark–recapture framework between 2010 and 2015 to estimate annual abundance, spatially explicit density, survival, recruitment, temporary movements, sex ratio and proportion of females breeding. We model metapopulation persistence with and without Corbett as a source within western Terai landscape at different levels of poaching and habitat connectivity. In 6 years, we recorded 6, 202 photo‐captures of 307 individual tigers. Annual tiger abundance and density were stable at 120 ( SE 19) and 14 ( SE 3) per 100 km 2 respectively. Detection probability of tigers was 0.18 ( SE 0.03) and detection‐corrected male:female sex ratio was female biased (0.80 SE 0.13). Apparent annual survival probability was 0.79 ( SE 0.05) for females and 0.60 ( SE 0.04) for males. Survival of tigers in CNP (0.68 SE 0.12) was lower than that reported for other populations. CNP tigers showed high reproduction with 54.8 ( SE 5.1)% females breeding and with addition of 35 ( SE 8)% as new recruits to the population each year. Small tiger populations in western Terai with moderate poaching could only persist through dispersal from CNP. Synthesis and applications . Corbett tiger population was characterized by a stable high density, high reproductive rate and low survival, resulting in high turnover rates (32%–48%) between successive years. Such source populations could sustain low‐level poaching and with habitat connectivity, recover tiger populations across the landscape. This study establishes potential thresholds that can likely be achieved by tiger populations under optimal natural conditions and highlights the importance of prioritizing conservation of source populations within tiger landscapes. This information can be used to plan and implement realistic tiger recovery programmes globally. Abstract : Corbett tiger population was characterized by a stable high density, high reproductive rate and low survival, resulting in high turnover rates (32%–48%) between successive years. Such source populations could sustain low‐level poaching and with habitat connectivity, recover tiger populations across the landscape. This study establishes potential thresholds that can likely be achieved by tiger populations under optimal natural conditions and highlights the importance of prioritizing conservation of source populations within tiger landscapes. This information can be used to plan and implement realistic tiger recovery programmes globally. सार: १) हमने भारतीय तराई भूभाग में स्तिथ कॉर्बेट राष्ट्रीय उद्यान में बाघों के जनांकिकी का अध्यन किया, जिसके माध्यम से बाघ संरक्षण की प्राथमिकता वाली महत्वपूर्ण बाघ आबादियों के लिए संभावित रणनीति का सुझाव दिया गया है I २) हमने छह वर्षों में ५२१ वर्ग कि०मी०. के छेत्र में रिमोट कैमरा ट्रैप के माध्यम से सैंपलिंग कर बाघों की आबादी और उनकी दीर्घ काल तक के जीवन क्षमता का अध्यन किया. हमने वैज्ञानिक "मार्क ‐रीकैप्चर " मॉडल के माध्यम से बाघों की गड़ना, उनकी उतर जीवित, भर्ती दर, लिंगानुपात, प्रजनन धारी मादा का सालाना प्रतिशत आँका. इस सुचना से हमने पॉपुलेशन वायबिलिटी विश्लेषण (प० व० वी०)के मॉडल्स बनाये और बाघों की पश्चिम तराई भूभाग से विलुप्त होने की सम्भावना का आंकलन किया। हमने इन प० व० वी० मॉडल्स में अलग‐अलग सन्दर्भ, जैसे की अवैध शिकार एवम बाघों के वास स्थलों के बीच के गलियारों के जुड़ाव इत्यादी को रखकर बाघों की दीर्घावधि तक सतत रहने की सम्भावना को बताया I ३) हमने छह वर्षों, में कुल ६२०२ बाघों के छायाचित्रों का संग्रह किया, जिनके विश्लेषण उपरांत कुल ३०७ बाघ पाए गए I इन छह वर्षों में बाघों की जनसँख्या घनत्व (१४ ± ३ प्रति १०० सक. की. मि.) स्थिर पाया गया एवम लिंगानुपात (नर प्रति मादा) ०.८० ± ०.१३ मुख्य रूप से मादा प्रभावी रहा I नरों की उतर जीवित ६० % और मादा की ८० % पायी गयी. कॉर्बेट राष्ट्रीय उद्यान में बाघों की उच्च प्रजनन क्षमता पायी गयी, जहाँ सालाना कुल प्रजनन धरी मादा ५५% पायी गयीं एवम नए बाघों का भर्ती दर ३५% प्राप्त किया गया I ४) कॉर्बेट की जनसँख्या की विशेषता स्थिर उच्च घनत्व, उच्च प्रजनन दर और कम उतर जीवित और उच्च स्तरीय बदलाव(टर्न ओवर) (३२‐४८%) है I इस तरह की स्रोत आबादी छोटे स्तर पर अवैध शिकार को बर्दाश्त कर सकती है, और यदि बाघों के निवास स्थान के बीच के गलियारों को संरक्षित रखा जाए तो सम्पूर्ण भूभाग में बाघों की आबादी को पुनर्प्राप्त कर सकती है I हमारे इस अध्यन में उन सारे मापदंडों का विश्लेषण किया गया है जो प्राकृतिक परिस्थितियों में बाघ आबादी द्वारा प्राप्त किया जा सकता है I हमारा अध्यन इस स्रोत आबादी के संरक्षण को प्राथमिकता देने के महत्व पर प्रकाश डालता है I इस अध्यन से प्राप्त सूचना का प्रयोग विश्व सत्तर पर बाघों के पुनर्व्यास की योजना बनाने के लिए उपयोग किया जा सकता है I